2009
DOI: 10.1534/genetics.108.099382
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interactions Between Regulators of Chlamydomonas Phosphorus and Sulfur Deprivation Responses

Abstract: The Chlamydomonas reinhardtii PSR1 gene is required for proper acclimation of the cells to phosphorus (P) deficiency. P-starved psr1 mutants show signs of secondary sulfur (S) starvation, exemplified by the synthesis of extracellular arylsulfatase and the accumulation of transcripts encoding proteins involved in S scavenging and assimilation. Epistasis analysis reveals that induction of the S-starvation responses in P-limited psr1 cells requires the regulatory protein kinase SNRK2.1, but bypasses the membrane-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…In contrast to wild-type cells, the sac1 mutant only accumulates SLT1, SLT2, and SULTR2 transcripts 24 h after the imposition of S starvation. This is consistent with the model proposed by Moseley et al (2009), in which SAC1 is a sensor that resides on the plasma membrane and acts as a negative regulator of the SNRK2.2 repressor protein kinase when environmental SO 4 22 levels fall below a certain threshold. This causes derepression of the S-responsive genes, including those encoding SO 4 22 transporters.…”
Section: Transcriptional Regulation Of So 4 22 Transporterssupporting
confidence: 92%
“…In contrast to wild-type cells, the sac1 mutant only accumulates SLT1, SLT2, and SULTR2 transcripts 24 h after the imposition of S starvation. This is consistent with the model proposed by Moseley et al (2009), in which SAC1 is a sensor that resides on the plasma membrane and acts as a negative regulator of the SNRK2.2 repressor protein kinase when environmental SO 4 22 levels fall below a certain threshold. This causes derepression of the S-responsive genes, including those encoding SO 4 22 transporters.…”
Section: Transcriptional Regulation Of So 4 22 Transporterssupporting
confidence: 92%
“…This supported the findings of previous work, where the LHCBM9 gene was not found to be up-regulated upon N deprivation Miller et al 2007;Moseley et al 2009), but contradicted a recent study by Grewe et al (2014), who found that N deprivation induced LHCBM9 protein expression. It is possible that LHCBM9 is regulated by N deprivation at a level other than transcription, especially since N-dependent gene regulation shares regulatory elements with the S-response pathway (Kopriva and Rennenberg 2004;Shin 2011).…”
Section: Discussionsupporting
confidence: 85%
“…B and C, RT-qPCR showing the levels of SULTR2, SLT1, SLT2, AOT4, SULTR1, ARS1, ARS2, ECP76, SBDP, LHCBM9, HAP2, and OASTL transcripts in the snrk2.2 single mutant (B) and snrk2.2 ars73a double mutant (C). Davies et al, 1994Davies et al, , 1996Davies et al, , 1999Yildiz et al, 1994Yildiz et al, , 1996Takahashi et al, 2001;Zhang et al, 2004;Chang et al, 2005;González-Ballester et al, 2008Moseley et al, 2009;Pootakham et al, 2010), and one of the first responses of this alga to S limitation was shown to be the activation of genes encoding high-affinity SO 4 22 transporters González-Ballester et al, 2010;Pootakham et al, 2010). Increased expression from high-affinity SO 4 22 transporters has been noted to occur within 30 min of the removal of S from the culture medium ( Fig.…”
Section: Discussionmentioning
confidence: 89%